The effect of lone motherhood on the smoking behaviour of young adults - Marco Francesconi; Stephen P. Jenkins; Thomas Siedler (Institute for the Study of Labor (IZA), 2009)
We provide evidence that living with an unmarried mother during childhood raises smoking propensities for young adults in Germany.
urn:nbn:de:101:1-20091009939
Keywords: I10; J12; J18; 330; Smoking; lone parent; childhood family structure; divorce; unobserved heterogeneity; Rauchen; Jugendliche; Mütter; Alleinerziehende; Deutschland